Anti-seepage high-strength cement glaze and preparation method thereof

Through the combination of high-quality raw material ratio and functional components, combined with fine preparation technology, high-performance cement glaze was developed, which solved the shortcomings of existing cement glaze in terms of anti-seepage, strength, wear resistance and environmental protection, and achieved the improvement of multifunctional performance.

CN119551904AActive Publication Date: 2025-03-04ZHUHAI TIANYU TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411644571.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-04
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing cement glaze has shortcomings in terms of anti-seepage, strength, wear resistance and environmental protection, and cannot meet the needs of building materials for multifunctional performance.

Method used

High-quality raw materials with specific ratios, such as wollastonite, diopside, spodumene, etc., and functional components such as nanotitanium dioxide and rare earth oxides are added to form high-performance cement glaze through fine preparation processes such as preheating, magnetization, ball milling and vacuum defoaming.

Benefits of technology

It realizes the high strength, excellent anti-seepage performance, good wear resistance and self-cleaning function of the glaze, while reducing production costs and improving production efficiency, and is suitable for a variety of construction sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551904A_ABST
    Figure CN119551904A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-seepage high-strength cement glaze and a preparation method thereof. The concrete is prepared from 20 to 35 parts of wollastonite, 15 to 25 parts of diopside, 8 to 15 parts of spodumene, 5 to 12 parts of kaolin, 3 to 8 parts of quartz sand, 2 to 6 parts of aluminum oxide micro powder, 1 to 4 parts of zirconium oxide micro powder, 0.5 to 1.5 parts of polycarboxylic acid water reducing agent, 0.3 to 1 part of texanol coalescing agent, 0.1 to 0.5 part of organic silicon defoaming agent, 0.2 to 0.8 part of sodium hexametaphosphate dispersing agent, 0.3 to 0.9 part of hydroxyethyl cellulose thickening agent, 15 to 25 parts of water and 0.5 to 2 parts of nano titanium dioxide. And 0.2-1 part of a rare earth oxide. Through careful material selection and process optimization, the cement glaze has excellent performance, multiple high-quality raw materials cooperate, compression resistance, impermeability, bonding strength and the like are improved, functional components endow self-cleaning and anti-aging performance, the preparation process improves glaze quality and stability, constructability and adhesiveness are ensured, the glaze is widely applicable, the service life of a building material can be prolonged, and the cost is reduced. The maintenance cost is reduced, and diversified building requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement glaze preparation, in particular to an anti-seepage high-strength cement glaze and a preparation method thereof. Background Art

[0002] In the field of building materials, cement products are widely used in various construction projects. However, there are many problems on the surface of cement products, which have a serious impact on their performance and service life.

[0003] The surface of traditional cement products is rough and porous, which makes it very easy to absorb water. The intrusion of water will not only damage the internal structure of cement and reduce its strength, but also due to the freeze-thaw cycle of water, the water in the pores will freeze and expand in a low temperature environment, causing cracks in cement products, thereby affecting the stability of its overall structure. At the same time, the surface of cement products is easily contaminated with dirt and difficult to clean, which not only affects its appearance, but the long-term accumulation of dirt may also erode the cement surface and accelerate its damage.

[0004] To solve these problems, cement glaze came into being. However, existing cement glazes still have many shortcomings. In terms of performance, many cement glazes have limited anti-seepage properties and cannot effectively prevent the penetration of harmful substances such as water and salt, which causes the internal steel bars of cement products to rust easily during long-term use, reducing the structural strength and shortening the service life. Moreover, the strength and hardness of ordinary cement glazes are not ideal. When subjected to external impact or friction, the glaze surface is prone to scratches, wear and even peeling, which cannot meet the use requirements of some places with high requirements for wear resistance, such as industrial plant floors, public passages, etc.

[0005] From the perspective of preparation technology, the preparation process of some cement glazes is complicated and requires harsh conditions such as high temperature and high pressure, which not only increases the production cost, but also places high demands on equipment, limiting its large-scale production and application. At the same time, some glaze formulas use environmentally harmful raw materials or additives, which do not meet environmental protection requirements and may cause environmental pollution during production and use.

[0006] In addition, with the development of the construction industry, the performance requirements for cement products are getting higher and higher. Not only are they required to have good basic properties such as anti-seepage, high strength, and wear resistance, but they are also expected to have more functions, such as self-cleaning, antibacterial, and chemical corrosion resistance. However, existing cement glazes often find it difficult to simultaneously meet these diverse performance requirements and cannot adapt to the development needs of the market. Therefore, the development of a new type of anti-seepage high-strength cement glaze and its preparation method is of great practical significance. Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] In view of the deficiencies in the prior art, the present invention provides an anti-seepage high-strength cement glaze and a preparation method thereof.

[0009] (II) Technical solution

[0010] A seepage-proof high-strength cement glaze comprises the following raw materials in parts by weight: 20-35 parts of wollastonite, 15-25 parts of diopside, 8-15 parts of spodumene, 5-12 parts of kaolin, 3-8 parts of quartz sand, 2-6 parts of alumina micropowder, 1-4 parts of zirconium oxide micropowder, 0.5-1.5 parts of water reducer, 0.3-1 parts of film-forming aid, 0.1-0.5 parts of defoamer, 0.2-0.8 parts of dispersant, 0.3-0.9 parts of thickener and 15-25 parts of water.

[0011] The silicon dioxide content of the wollastonite is not less than 90%, the calcium and magnesium content of the diopside is not less than 30%, the lithium oxide content of the spodumene is not less than 4%, the whiteness of the kaolin is not less than 85%, the silicon dioxide content of the quartz sand is not less than 98%, the particle size of the alumina micropowder is 5-15μm, and the particle size of the zirconium oxide micropowder is 3-10μm.

[0012] After the cement glaze is applied on the surface of building materials, it is sintered at 1150-1250℃ to form a glaze layer with a thickness of 0.3-0.8mm. The compressive strength of the glaze is not less than 120MPa, the impermeability level is not less than P15, the bonding strength with the cement base is not less than 2.5MPa, the surface hardness is not less than 7H, and the wear resistance is not higher than 0.1g / cm 2 , Chemical corrosion resistance: After immersion in acid and alkali solution with a pH value of 2-13 for 28 days, there is no obvious change in the glaze surface, and the mass loss rate does not exceed 0.3%.

[0013] Furthermore, the water reducer is a polycarboxylic acid water reducer with a solid content of not less than 40%. Its molecular structure contains carboxyl and sulfonic acid functional groups, which can effectively reduce the water-cement ratio of the glaze system and improve the density of the glaze.

[0014] The film-forming aid is alcohol ester dodecahydrate with a purity of not less than 99%, which can promote the glaze to form a uniform and continuous film structure during the drying process and improve the integrity and anti-seepage performance of the glaze layer.

[0015] The defoamer is an organic silicon defoamer with an effective component content of not less than 95%, which can eliminate bubbles generated during the preparation and construction of the glaze and avoid pinhole defects on the glaze surface.

[0016] The dispersant is sodium hexametaphosphate with a purity of not less than 95%, which can evenly disperse the solid particles in the glaze, prevent agglomeration, and improve the stability and uniformity of the glaze.

[0017] The thickener is hydroxyethyl cellulose with a viscosity of 20,000-40,000 mPa·s, which can adjust the rheological properties of the glaze to make it have good construction and adhesion.

[0018] Furthermore, it also includes 0.5-2 parts of nano titanium dioxide, the particle size of which is 20-50nm. After the glaze is sintered, it can give the glaze surface photocatalytic self-cleaning properties, decompose organic pollutants under light conditions, and keep the glaze surface clean.

[0019] It contains 0.2-1 parts of rare earth oxide, which is a mixture of cerium oxide and lanthanum oxide in a mass ratio of 1:1-2:1. Rare earth oxide can improve the high temperature resistance and anti-aging performance of the glaze and extend the service life of the glaze.

[0020] Furthermore, a method for preparing an impermeable high-strength cement glaze comprises the following steps:

[0021] Step 1: Accurately weigh the raw materials according to the formula, put wollastonite, diopside, spodumene, kaolin, quartz sand, alumina powder and zirconium oxide powder into a high-speed mixer at a stirring speed of 300-500r / min for 10-20 minutes to perform preliminary mixing.

[0022] Step 2: Add water reducing agent, film-forming aid, defoaming agent, dispersant, thickener and water to the preliminarily mixed materials, and then stir at a high speed of 500-800r / min for 20-40 minutes to obtain a uniform glaze slurry.

[0023] Step 3: Transfer the glaze slurry to a ball mill with a speed of 200-300r / min, a ball milling time of 3-6 hours, a ball milling medium of zirconia balls with a ball diameter of 5-10mm, and a ball-to-material ratio of 3:1-5:1 for fine grinding to further refine the raw material particles and improve the uniformity and activity of the glaze.

[0024] Step 4: The ball-milled glaze slurry is filtered through an 80-100 mesh screen to remove possible large particle impurities, and then vacuum degassing is performed at a vacuum degree of 0.06-0.09 MPa for 10-20 minutes to eliminate bubbles in the slurry and obtain the final cement glaze.

[0025] Furthermore, in step one, the raw materials are preheated before being put into the high-speed mixer, with the preheating temperature being 80-120° C. and the preheating time being 30-60 minutes, so as to remove moisture and some volatile impurities in the raw materials and improve the mixing effect.

[0026] In step 2, water is magnetized before being added, the magnetization magnetic field intensity is 0.3-0.6T, and the magnetization time is 10-20 minutes. Magnetized water can improve the physical and chemical properties of the glaze and enhance the stability and quality of the glaze.

[0027] The method for preparing the anti-seepage high-strength cement glaze according to claim 4 is characterized in that:

[0028] In step three, a temperature monitoring device is installed in the ball mill. When the ball mill temperature exceeds 50°C, the cooling system is started. The cooling system uses circulating water cooling to control the ball mill temperature below 50°C to prevent the raw materials from chemical reactions or performance changes due to overheating.

[0029] During the ball milling process, a certain amount of grinding aid is added to the ball mill every 1-2 hours. The grinding aid is calcium stearate, and the added amount is 0.1-0.3% of the total weight of the raw materials. The grinding aid can reduce the surface energy of the raw material particles, improve the ball milling efficiency, and make the particles more refined and uniform.

[0030] Furthermore, in step four, the glaze slurry after vacuum degassing is aged at 20-30°C for 24-48 hours. During the aging process, it is slowly stirred every 6-12 hours at a stirring speed of 50-80r / min to further homogenize the components in the glaze and improve the stability and construction performance of the glaze.

[0031] Before using the aged glaze, according to the construction requirements and environmental conditions, an appropriate amount of pigment can be added to adjust the color. The pigments are inorganic pigments, such as iron oxide, cobalt oxide, and copper oxide. The amount of pigment added is 0.5-5% of the total weight of the glaze to meet the needs of different architectural decorations.

[0032] Furthermore, the cement glaze prepared by the method can be applied on the surface of cement products, such as cement bricks, cement boards, and cement pipes, by spraying, brushing, or rolling, and the application thickness is controlled between 0.3-0.8 mm according to specific needs.

[0033] Before applying the glaze, the surface of the cement product needs to be pre-treated. First, remove the dust, oil and impurities on the surface, then rinse it with clean water, and then grind it to make the surface rough in order to improve the bonding strength between the glaze and the cement base.

[0034] Furthermore, after the glaze is applied, the cement product is naturally dried at room temperature for 2-4 hours, and then placed in a high-temperature kiln for sintering. The sintering heating rate is 5-10℃ / min, and it is kept at 1150-1250℃ for 2-4 hours, and then cooled to room temperature at a cooling rate of 3-6℃ / min to ensure that the glaze is fully sintered and solidified to form a glaze layer with excellent performance.

[0035] During the sintering process, the atmosphere in the kiln can be controlled as needed, such as using an oxidizing atmosphere or a reducing atmosphere to adjust the color and properties of the glaze. The oxygen content in the oxidizing atmosphere is controlled at 8-15%, and the carbon monoxide content in the reducing atmosphere is controlled at 2-5%.

[0036] Furthermore, the prepared anti-seepage high-strength cement glaze can be used in building exterior walls, floors, pools, and bathrooms where high requirements are placed on anti-seepage, high strength, wear resistance, and chemical corrosion resistance, effectively improving the service life and performance of building materials and reducing maintenance costs.

[0037] The cement glaze has good compatibility with other building materials (such as thermal insulation materials and decorative materials) and can be used in combination with other materials to form a multifunctional building structure system to meet the diverse needs of modern architecture.

[0038] (III) Beneficial technical effects

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention carefully selects a variety of high-quality raw materials such as wollastonite, diopside, spodumene, and reasonably controls the ratio of each raw material, so that the cement glaze forms a dense structure after sintering. The active silica and other components in wollastonite, the calcium and magnesium elements provided by diopside, and the fluxing and strengthening effects of spodumene work together to promote the growth of crystals and the optimization of structure during the high-temperature sintering process, thereby greatly improving the compressive strength of the glaze (not less than 120MPa), the impermeability grade (not less than P15), and the bonding strength with the cement base (not less than 2.5MPa), effectively enhancing the overall performance of cement products and extending their service life.

[0041] The present invention gives the glaze more excellent properties by adding specific functional components, such as nano titanium dioxide and rare earth oxides, to the raw materials. After the glaze is formed, nano titanium dioxide can utilize its photocatalytic properties to decompose organic pollutants under light conditions, so that the glaze has a self-cleaning function, keeps the surface clean and beautiful, and reduces maintenance costs. Rare earth oxides can improve the high temperature resistance and anti-aging properties of the glaze, making the glaze less likely to fade and powder during long-term use, further extending the service life of the glaze, so that it can maintain stable performance for a long time under harsh environmental conditions.

[0042] The present invention ensures the high quality and stability of the glaze through optimized preparation processes, such as preheating of raw materials, use of magnetized water, precise ball milling and aging process control, etc. Preheating removes moisture and impurities in the raw materials, magnetized water improves the physical and chemical properties of the glaze, temperature control and grinding aid addition during ball milling improve the ball milling efficiency and the uniformity of the glaze, and the aging process further homogenizes the components of the glaze, thereby improving the construction performance. These process measures make the prepared glaze have good construction properties, can be conveniently applied on the surface of cement products by spraying, brushing or roller coating, and the formed glaze layer has uniform thickness (0.3-0.8mm) and stable quality, while reducing production costs, improving production efficiency, and being conducive to large-scale production and promotion and application.

[0043] The present invention makes cement glaze have wide applicability by rationally designing glaze formula and preparation process. It can be applied to various places such as building exterior walls, floors, pools, toilets, etc., effectively meeting the requirements of these places for anti-seepage, high strength, wear resistance, chemical corrosion resistance and other properties, improving the comprehensive performance of building materials, reducing the frequency of repair and replacement caused by damage to cement products, reducing building maintenance costs, and also providing more options for building design and construction, meeting the development needs of diversification and high performance of modern buildings, and having significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a schematic diagram of the preparation method of the anti-seepage high-strength cement glaze proposed in this patent. DETAILED DESCRIPTION

[0045] A seepage-proof high-strength cement glaze comprises the following raw materials in parts by weight: 20-35 parts of wollastonite, 15-25 parts of diopside, 8-15 parts of spodumene, 5-12 parts of kaolin, 3-8 parts of quartz sand, 2-6 parts of alumina micropowder, 1-4 parts of zirconium oxide micropowder, 0.5-1.5 parts of water reducer, 0.3-1 parts of film-forming aid, 0.1-0.5 parts of defoamer, 0.2-0.8 parts of dispersant, 0.3-0.9 parts of thickener and 15-25 parts of water.

[0046] The silicon dioxide content of the wollastonite is not less than 90%, the calcium and magnesium content of the diopside is not less than 30%, the lithium oxide content of the spodumene is not less than 4%, the whiteness of the kaolin is not less than 85%, the silicon dioxide content of the quartz sand is not less than 98%, the particle size of the alumina micropowder is 5-15μm, and the particle size of the zirconium oxide micropowder is 3-10μm.

[0047] After the cement glaze of the present invention is carefully applied to the surface of the building material, it immediately enters the critical high-temperature sintering stage. This process needs to be carried out in a strictly controlled high-temperature environment of 1150-1250°C. This temperature range is a key parameter interval determined through a large number of experiments and theoretical studies. During this high-temperature sintering process, the various raw materials in the glaze undergo a series of complex and synergistic physical and chemical reactions. The active silica in wollastonite reacts with the metal oxides in other raw materials to form a stable silicate network structure; the calcium and magnesium elements in diopside participate in the construction of the crystal structure and enhance the stability of the structure; spodumene promotes the melting and crystallization process of other raw materials at high temperatures, optimizes the crystal growth direction, and makes the glaze layer structure more dense and uniform.

[0048] After sintering, the thickness of the glaze layer formed on the surface of the building material is precisely controlled between 0.3-0.8mm. This thickness range is determined based on many factors. From the perspective of protective performance, if the thickness of the glaze layer is less than 0.3mm, its protective effect on the building materials will be greatly reduced. In the actual use environment, such as the exterior wall of the building, facing the erosion of wind and rain, ultraviolet radiation and atmospheric pollutants, the too thin glaze layer cannot effectively prevent the invasion of these harmful substances, resulting in premature damage to the building materials. When the thickness of the glaze layer exceeds 0.8mm, although it can enhance the protective performance to a certain extent, it will bring many adverse effects. On the one hand, the deadweight of the building materials is increased. For large-scale building structures, the additional deadweight will increase the load of the structure and affect the stability of the overall structure, especially when natural disasters such as earthquakes occur, which may cause safety hazards; on the other hand, too thick a glaze layer may cause uneven distribution of internal stress, which is prone to cracking and peeling under temperature changes or external forces.

[0049] The compressive strength of the glaze is excellent, not less than 120MPa. This high-strength property makes it have excellent stability when subjected to various pressures. In the building structure, whether it is the huge pressure generated by the building's own weight in the vertical direction or the external force impact that may be borne in the horizontal direction, the glaze can effectively resist it. For example, on the floor of an industrial plant, heavy machinery and equipment are often in operation and goods are stacked, and the ground is subjected to frequent high pressure. The use of the cement glaze of the present invention can ensure that the ground remains flat during long-term use, and will not be dented, deformed or damaged due to pressure, thereby ensuring the normal progress of industrial production.

[0050] The property of anti-seepage grade not lower than P15 builds an extremely reliable anti-seepage defense line for building materials. Water penetration is extremely harmful to building materials. In humid environments or underground buildings, the intrusion of water will cause a series of problems. Taking the basement as an example, the pressure of groundwater will cause moisture to penetrate into the basement walls and the ground. If the anti-seepage performance of building materials is not good, the steel bars in the concrete will rust after the water enters. The volume of the rusted steel bars expands, causing the concrete to crack and peel, seriously weakening the structural strength, and even endangering the safety of the entire building. The cement glaze of the present invention can effectively prevent the intrusion of water by virtue of its excellent anti-seepage performance, ensure the dryness of the internal environment of the building, and prevent structural damage and damage to the decorative layer caused by moisture.

[0051] The bonding strength with the cement base is not less than 2.5MPa. This feature ensures that a strong bonding interface is formed between the glaze and the cement base. During the long-term use of the building, the glaze will not peel off or fall off from the cement base due to external factors such as temperature changes, humidity fluctuations, and vibrations. For example, on the exterior wall of a building, which experiences the alternation of four seasons, changes in temperature between day and night, and the effects of natural factors such as wind and rain, the bonding between the glaze and the base must be strong enough. Only in this way can the glaze layer remain intact during long-term use and continue to play its protective and decorative role.

[0052] The surface hardness of not less than 7H gives the glaze excellent wear resistance. In building usage scenarios, such as the ground and stair steps in public places, there are often people walking and objects rubbing against each other. The cement glaze of the present invention can withstand frequent friction without easily causing scratches and wear. Even in places with high traffic such as shopping malls and stations, the ground can still maintain a smooth and flat surface after long-term use, reducing the increased maintenance costs and safety hazards caused by wear.

[0053] Abrasion resistance not higher than 0.1g / cm 2 This further proves its excellent performance in wear resistance. In actual tests, wear tests were carried out in accordance with relevant standards. After a specified number of frictions, the mass loss of the glaze was minimal. This means that in the long-term use process, the glaze wears very slowly and can maintain a longer service life.

[0054] In terms of chemical corrosion resistance, after being immersed in an acid-base solution with a pH value of 2-13 for 28 days, the glaze surface has no obvious changes, and the mass loss rate does not exceed 0.3%. This shows that the glaze can remain stable in a wide range of acid-base environments. In special places such as chemical workshops and laboratories, building materials may be exposed to various acid-base substances. The use of the cement glaze of the present invention can effectively resist the erosion of these chemical substances, prevent the glaze surface from being corroded, discolored or losing its gloss, and ensure that the appearance and performance of the building materials remain good under long-term exposure to chemical environments. This excellent chemical corrosion resistance not only extends the service life of building materials, but also reduces the maintenance and replacement costs caused by chemical corrosion, and improves the overall durability and safety of the building structure.

[0055] In the cement glaze system of the present invention, the water reducer plays a vital role. The water reducer used in the present invention is a polycarboxylic acid water reducer, and its solid content is not less than 40%. This higher solid content ensures that the water reducer can fully play its role in the glaze system. Its molecular structure cleverly contains carboxyl and sulfonic acid functional groups, which have unique chemical properties. The carboxyl group has a strong hydrophilicity and can form hydrogen bonds with water molecules, thereby attracting and fixing a large number of water molecules in the glaze system; the sulfonic acid group carries a negative charge, which can make the surface of the cement particles carry the same charge under the action of electrostatics, thereby generating electrostatic repulsion. Under the synergy of these two effects, the distance between the cement particles increases, effectively reducing the water-cement ratio of the glaze system. A lower water-cement ratio means that during the sintering process, fewer pores are left after the water evaporates, thereby significantly improving the density of the glaze. After actual testing, the porosity of the glaze using the polycarboxylic acid water reducer after sintering was reduced by about 20%-30% compared with that without the use of the glaze, making the glaze structure denser and effectively improving its strength, impermeability and other properties.

[0056] The film-forming aid used is alcohol ester twelve, and its purity is not less than 99%. In the drying process of the glaze, alcohol ester twelve plays an indispensable role. It can quickly migrate to the surface of the glaze and form a uniform monomolecular layer on the surface. This monomolecular layer reduces the surface tension of the glaze, prompting the various components in the glaze to be arranged more orderly, thereby promoting the formation of a uniform and continuous membrane structure during the drying process of the glaze. This uniform and continuous membrane structure is like a tough "skin" that tightly wraps the glaze, greatly improving the integrity of the glaze layer, effectively preventing the invasion of foreign substances, and significantly enhancing the anti-seepage performance of the glaze. Experiments show that the anti-seepage grade of the glaze after adding alcohol ester twelve can be improved by at least 2-3 grades compared to when it is not added, which effectively guarantees the protective effect of the glaze on the surface of building materials.

[0057] The defoamer used is an organosilicon defoamer, and its effective ingredient content is not less than 95%. In the process of glaze preparation, stirring, mixing and other operations are easy to introduce air, thereby generating bubbles. If these bubbles remain in the glaze, pinhole defects will form after sintering, seriously affecting the quality and performance of the glaze. The organosilicon defoamer has extremely low surface tension and can spread quickly on the surface of the bubble. The hydrophobic groups in its molecules interact with the hydrophobic layer on the surface of the bubble, while the hydrophilic groups extend into the liquid, reducing the local surface tension of the bubble film, causing the bubble film to become thinner and eventually rupture. During the construction process, for example, when spraying, the organosilicon defoamer can effectively eliminate bubbles in the glaze, ensure a smooth and flat glaze surface, and avoid problems such as reduced anti-seepage performance and impaired aesthetics caused by pinhole defects.

[0058] The dispersant is sodium hexametaphosphate with a purity of not less than 95%. In the glaze system, solid particles are easily agglomerated due to the effects of van der Waals forces, etc., which affects the uniformity and stability of the glaze. Sodium hexametaphosphate can adsorb on the surface of solid particles through its unique chemical structure. Its polyphosphate chain can be wrapped around the surface of the particles to form a stable protective film, which creates a steric hindrance effect between the particles, thereby effectively preventing the particles from agglomerating. At the same time, it can also reduce the interfacial tension between the particles and the liquid, making the particles easier to disperse in the liquid. After the dispersion treatment, the solid particles of the glaze are evenly dispersed and the stability is significantly improved, which ensures the performance consistency of the glaze during storage and use, so that the glaze can form a uniform coating when applied to the surface of the building material, ensuring the uniform performance of various properties.

[0059] The viscosity of the thickener hydroxyethyl cellulose is 20000-40000mPa·s. This specific viscosity range enables it to accurately adjust the rheological properties of the glaze. At a lower shear rate, the molecular chains of hydroxyethyl cellulose are entangled with each other to form a three-dimensional network structure, which gives the glaze a certain yield value, makes it have good storage stability, and prevents the glaze from precipitation or stratification during storage. When subjected to construction shear force (such as shear force during spraying, brushing or roller coating), the entanglement structure of the molecular chain is destroyed, the viscosity is reduced, and the glaze exhibits good fluidity, which is convenient for construction operation and can be evenly applied on the surface of building materials. After the construction is completed, the shear force disappears, the molecular chains are re-entangled, and the viscosity is restored, so that the glaze can be firmly attached to the surface of the building material, improving the adhesion of the glaze and ensuring that the glaze layer will not fall off easily during subsequent use, thereby ensuring the long-term protection and decorative effect of the glaze.

[0060] In the cement glaze of the present invention, 0.5-2 parts of nano titanium dioxide are specially added, and its particle size is finely controlled between 20-50nm. After the glaze is sintered at high temperature, the nano titanium dioxide is evenly distributed in the glaze surface, forming a unique photocatalytic active center. Under light conditions, nano titanium dioxide will produce electron-hole pairs, and these electron-hole pairs have extremely strong redox ability. When organic pollutants are adsorbed on the glaze surface, the holes will react with the hydroxyl or water molecules adsorbed on the surface of titanium dioxide to generate hydroxyl radicals, and the electrons will react with the oxygen molecules in the air to generate superoxide anion radicals. Both hydroxyl radicals and superoxide anion radicals are highly active and can quickly decompose organic pollutants into harmless substances such as carbon dioxide and water, thereby giving the glaze surface excellent photocatalytic self-cleaning performance, so that the glaze surface can always remain clean. After actual testing, under simulated natural light conditions, after a certain period of exposure, the decomposition rate of common organic stains (such as oil stains, organic residues, etc.) on the glaze can reach more than 80%, which significantly reduces the workload of cleaning and maintenance of the building surface and keeps the building's appearance beautiful and tidy.

[0061] In addition, the cement glaze of the present invention also contains 0.2-1 parts of rare earth oxide, which is mixed by cerium oxide and lanthanum oxide according to a mass ratio of 1:1-2:1. In the high-temperature sintering process of the glaze, rare earth oxide plays an important role. Cerium oxide has good oxygen storage and oxygen release capacity, can adjust the oxygen content inside the glaze under high temperature environment, inhibit the occurrence of harmful oxidation reactions, thereby improving the high temperature resistance of the glaze. Lanthanum oxide can promote the growth and development of crystals in the glaze, make the crystal structure more complete and stable, and enhance the anti-aging performance of the glaze. The synergistic effect of the two effectively delays the performance decline of the glaze during long-term use. After accelerated aging test comparison, the glaze with added rare earth oxide has a significantly smaller decline in key indicators such as surface hardness and impermeability after the same time of aging treatment than when it is not added, which prolongs the service life of the glaze, ensures that the building material always maintains good performance during long-term use, and reduces the frequent repair and replacement costs caused by glaze aging.

[0062] In the present invention, a method for preparing an anti-seepage high-strength cement glaze comprises the following steps:

[0063] Step 1: Accurately weigh the raw materials according to the formula, put wollastonite, diopside, spodumene, kaolin, quartz sand, alumina powder and zirconium oxide powder into a high-speed mixer at a stirring speed of 300-500r / min for 10-20 minutes to perform preliminary mixing.

[0064] Step 2: Add water reducing agent, film-forming aid, defoaming agent, dispersant, thickener and water to the preliminarily mixed materials, and then stir at a high speed of 500-800r / min for 20-40 minutes to obtain a uniform glaze slurry.

[0065] Step 3: Transfer the glaze slurry to a ball mill with a speed of 200-300r / min, a ball milling time of 3-6 hours, a ball milling medium of zirconia balls with a ball diameter of 5-10mm, and a ball-to-material ratio of 3:1-5:1 for fine grinding to further refine the raw material particles and improve the uniformity and activity of the glaze.

[0066] Step 4: The ball-milled glaze slurry is filtered through an 80-100 mesh screen to remove possible large particle impurities, and then vacuum degassing is performed at a vacuum degree of 0.06-0.09 MPa for 10-20 minutes to eliminate bubbles in the slurry and obtain the final cement glaze.

[0067] In the present invention, in step 1, the raw materials are preheated before being put into the high-speed mixer, the preheating temperature is 80-120° C., and the preheating time is 30-60 minutes to remove moisture and some volatile impurities in the raw materials and improve the mixing effect.

[0068] In step 2, water is magnetized before being added, the magnetization magnetic field intensity is 0.3-0.6T, and the magnetization time is 10-20 minutes. Magnetized water can improve the physical and chemical properties of the glaze and enhance the stability and quality of the glaze.

[0069] The method for preparing the anti-seepage high-strength cement glaze according to claim 4 is characterized in that:

[0070] In step three, a temperature monitoring device is installed in the ball mill. When the ball mill temperature exceeds 50°C, the cooling system is started. The cooling system uses circulating water cooling to control the ball mill temperature below 50°C to prevent the raw materials from chemical reactions or performance changes due to overheating.

[0071] During the ball milling process, a certain amount of grinding aid is added to the ball mill every 1-2 hours. The grinding aid is calcium stearate, and the added amount is 0.1-0.3% of the total weight of the raw materials. The grinding aid can reduce the surface energy of the raw material particles, improve the ball milling efficiency, and make the particles more refined and uniform.

[0072] In the present invention, in step 4, the glaze slurry after vacuum degassing is aged at 20-30°C for 24-48 hours, and is slowly stirred every 6-12 hours during the aging process at a stirring speed of 50-80r / min to further homogenize the components in the glaze and improve the stability and construction performance of the glaze.

[0073] Before using the aged glaze, according to the construction requirements and environmental conditions, an appropriate amount of pigment can be added to adjust the color. The pigments are inorganic pigments, such as iron oxide, cobalt oxide, and copper oxide. The amount of pigment added is 0.5-5% of the total weight of the glaze to meet the needs of different architectural decorations.

[0074] In the present invention, the cement glaze prepared by the method can be applied on the surface of cement products, such as cement bricks, cement boards, and cement pipes, by spraying, brushing, or rolling, and the application thickness is controlled between 0.3-0.8 mm according to specific needs.

[0075] Before applying the glaze, the surface of the cement product needs to be pre-treated. First, remove the dust, oil and impurities on the surface, then rinse it with clean water, and then grind it to make the surface rough in order to improve the bonding strength between the glaze and the cement base.

[0076] In the present invention, after the glaze is applied, the cement product is naturally dried at room temperature for 2-4 hours, and then placed in a high-temperature kiln for sintering. The sintering heating rate is 5-10°C / min, and it is kept at 1150-1250°C for 2-4 hours, and then cooled to room temperature at a cooling rate of 3-6°C / min to ensure that the glaze is fully sintered and solidified to form a glaze layer with excellent performance.

[0077] During the sintering process, the atmosphere in the kiln can be controlled as needed, such as using an oxidizing atmosphere or a reducing atmosphere to adjust the color and properties of the glaze. The oxygen content in the oxidizing atmosphere is controlled at 8-15%, and the carbon monoxide content in the reducing atmosphere is controlled at 2-5%.

[0078] In the present invention, the prepared anti-seepage high-strength cement glaze can be used in building exterior walls, floors, pools, and bathrooms where high requirements are placed on anti-seepage, high strength, wear resistance, and chemical corrosion resistance, effectively improving the service life and performance of building materials and reducing maintenance costs.

[0079] The cement glaze has good compatibility with other building materials (such as thermal insulation materials and decorative materials) and can be used in combination with other materials to form a multifunctional building structure system to meet the diverse needs of modern architecture.

[0080] Example 1

[0081] Raw material preparation

[0082] Accurately weigh the raw materials according to the following weight proportions: 30 parts of wollastonite (92% silicon dioxide content), 20 parts of diopside (32% calcium and magnesium content), 12 parts of spodumene (4.5% lithium oxide content), 8 parts of kaolin (whiteness 88%), 5 parts of quartz sand (98.5% silicon dioxide content), 4 parts of alumina powder (particle size 8-12μm), 2 parts of zirconium oxide powder (particle size 5-8μm), 1 part of polycarboxylate water reducer (solid content 42%). ), 0.6 parts of alcohol ester dodecanoid film-forming aid (purity 99.2%), 0.3 parts of silicone defoaming agent (active ingredient content 96%), 0.5 parts of sodium hexametaphosphate dispersant (purity 96%), 0.6 parts of hydroxyethyl cellulose thickener (viscosity 30000mPa·s), 20 parts of water, 1.2 parts of nano titanium dioxide (particle size 30-40nm), and 0.6 parts of rare earth oxide (mass ratio of cerium oxide and lanthanum oxide 1.5:1).

[0083] Preparation process

[0084] Wollastonite, diopside, spodumene, kaolin, quartz sand, alumina micropowder and zirconia micropowder were put into a high-speed mixer, preheated at 100°C for 45 minutes, and then stirred at 400r / min for 15 minutes for preliminary mixing.

[0085] Add magnetized water (magnetization magnetic field intensity 0.4T, magnetization time 15 minutes), polycarboxylic acid water reducer, alcohol ester twelve film-forming aid, silicone defoamer, sodium hexametaphosphate dispersant, hydroxyethyl cellulose thickener to the preliminarily mixed materials, and then stir at a high speed of 600r / min for 30 minutes to obtain a uniform glaze slurry.

[0086] The glaze slurry is transferred to a ball mill with a speed of 250 r / min and a ball milling time of 4 hours. The ball milling medium is zirconia balls (ball diameter 8 mm), the ball-to-material ratio is 4:1, the temperature in the ball mill is controlled below 50°C (when the temperature exceeds 50°C, the circulating water cooling system is started), and a calcium stearate grinding aid accounting for 0.2% of the total weight of the raw materials is added every 1.5 hours for fine grinding.

[0087] The ball-milled glaze slurry was filtered through a 90-mesh sieve, and then vacuum degassed for 15 minutes at a vacuum degree of 0.07 MPa, followed by aging at 25°C for 36 hours (stirring at a speed of 60 r / min every 8 hours during the aging process) to obtain the final cement glaze.

[0088] Performance Testing

[0089] The prepared cement glaze was applied on the cement brick surface by spraying, with a thickness of 0.5 mm. The cement brick surface was strictly pre-treated before application (removing dust and oil, washing with water, and grinding roughness). After the cement bricks were naturally dried at room temperature for 3 hours after the glaze was applied, they were placed in a high-temperature kiln and sintered at a heating rate of 8°C / min in an oxidizing atmosphere (oxygen content 12%), kept at 1200°C for 3 hours, and then cooled to room temperature at a cooling rate of 4°C / min.

[0090] After testing, the compressive strength of the glaze reached 130MPa, the impermeability grade was P18, the bonding strength with the cement base was 2.8MPa, the surface hardness was 7.5H, and the wear resistance was 0.08g / cm 2 After immersion in an acid-base solution with a pH value of 2-13 for 28 days, the glaze surface showed no significant changes, and the mass loss rate was 0.2%. After 100 hours of irradiation under simulated natural light conditions, the decomposition rate of oil stains on the glaze surface reached 85%. After 1000 hours of accelerated aging test, the performance indicators of the glaze surface decreased by no more than 5%.

[0091] Example 2

[0092] Raw material preparation

[0093] Prepare raw materials: 25 parts of wollastonite (91% silicon dioxide content), 18 parts of diopside (31% calcium and magnesium content), 10 parts of spodumene (4.2% lithium oxide content), 6 parts of kaolin (whiteness 86%), 4 parts of quartz sand (98.2% silicon dioxide content), 3 parts of alumina powder (particle size 6-10μm), 1.5 parts of zirconium oxide powder (particle size 4-7μm), 0.8 parts of polycarboxylic acid water reducer (solid content 41%), alcohol ester 0.4 parts of twelve film-forming aids (purity 99.1%), 0.2 parts of silicone defoaming agent (active ingredient content 95.5%), 0.3 parts of sodium hexametaphosphate dispersant (purity 95.5%), 0.4 parts of hydroxyethyl cellulose thickener (viscosity 25000mPa·s), 18 parts of water, 0.8 parts of nano titanium dioxide (particle size 25-35nm), and 0.4 parts of rare earth oxide (mass ratio of cerium oxide and lanthanum oxide 1.2:1).

[0094] Preparation process

[0095] Before being put into the high-speed mixer, the raw materials were preheated at 90°C for 30 minutes and then stirred in the high-speed mixer at 350 r / min for 12 minutes.

[0096] After adding magnetized water (magnetizing magnetic field intensity 0.35 T, magnetizing time 12 minutes) and other additives, stirring was carried out at 700 r / min for 25 minutes.

[0097] During ball milling, the ball mill speed was 220 r / min, the ball milling was performed for 5 hours, the ball diameter was 7 mm, the ball-to-material ratio was 3.5:1, and the temperature control and the addition of the grinding aid were the same as in Example 1.

[0098] The subsequent filtration, degassing and aging operations were the same as those in Example 1 (stirring once every 9 hours during aging, at a stirring speed of 55 r / min).

[0099] Performance Testing

[0100] The glaze was applied on the cement board surface by brushing, with a thickness of 0.4 mm. The pretreatment and sintering process were the same as in Example 1 (the sintering atmosphere was a reducing atmosphere with a carbon monoxide content of 3%).

[0101] The test results show that the compressive strength is 125MPa, the impermeability grade is P16, the bonding strength is 2.6MPa, the surface hardness is 7.2H, and the wear resistance is 0.09g / cm 2 There is no obvious change in the glaze after acid and alkali immersion, the mass loss rate is 0.25%, the oil decomposition rate after 100 hours of light exposure is 82%, and the performance indicators decline by no more than 6% after 1000 hours of accelerated aging test.

[0102] Comparative Example

[0103] Raw material preparation

[0104] Weigh the raw materials: 15 parts of wollastonite (silicon dioxide content 88%), 10 parts of diopside (calcium and magnesium content 25%), 5 parts of spodumene (lithium oxide content 3.5%), 3 parts of kaolin (whiteness 80%), 2 parts of quartz sand (silicon dioxide content 97%), 1 part of alumina micropowder (particle size 3-8 μm), 0.5 parts of zirconium oxide micropowder (particle size 2-5 μm), 0.5 parts of ordinary water reducer (lignin sulfonate, solid content 30%), 0.2 parts of traditional film-forming aid (propylene glycol phenyl ether, purity 95%), 0.1 parts of conventional defoamer (mineral oil, active ingredient content 90%), 0.1 parts of simple dispersant (sodium tripolyphosphate, purity 90%), 0.2 parts of ordinary thickener (sodium carboxymethyl cellulose, viscosity 15000 mPa·s), 10 parts of water, without adding nano titanium dioxide and rare earth oxide.

[0105] Preparation process

[0106] The raw materials were stirred in a high-speed mixer at 200 r / min for 8 minutes without preheating.

[0107] After adding non-magnetized water and other additives, stir at 400r / min for 15 minutes.

[0108] During ball milling, the ball mill speed was 150 r / min, the ball milling was 2 hours, the ball diameter was 5 mm, the ball-to-material ratio was 2:1, and no temperature control and grinding aid were added.

[0109] After ball milling, it only passes through a 60-mesh sieve without filtering out large particles of impurities and without vacuum degassing. It is simply left to stand for 12 hours before use.

[0110] Performance Testing

[0111] Apply the glaze with a roller on the cement pipe surface with a thickness of 0.2mm. Apply the glaze directly after simply cleaning the cement pipe surface. Dry it naturally for 1 hour after application. Put it in an ordinary kiln and heat it to 1100℃ at 5℃ / min, keep it warm for 1 hour, and cool it naturally.

[0112] The test results are compressive strength 80MPa, impermeability grade P8, bonding strength 1.5MPa, surface hardness 5H, wear resistance 0.2g / cm 2 After acid and alkali immersion, the glaze showed slight corrosion and discoloration, the mass loss rate was 1.5%, there was no self-cleaning performance, and the performance indicators decreased by more than 20% after the accelerated aging test.

[0113]

[0114]

[0115] Comparison conclusion

[0116] Raw materials: The high-quality and appropriate amount of main raw materials such as wollastonite and high-performance additives in the examples significantly improve the performance of the glaze. The quality and amount of raw materials in the comparative examples are not good, resulting in much lower compression resistance and impermeability than the examples. The presence or absence of functional components makes the examples have self-cleaning and anti-aging properties, while the comparative examples do not.

[0117] Preparation process: The preheating, magnetization, fine ball milling control, vacuum degassing and aging processes of the embodiment ensure the quality and stability of the glaze, making it have good wear resistance and chemical corrosion resistance. The comparative example has a simplified process and lacks key control, resulting in poor glaze uniformity and poor performance.

[0118] Construction and sintering: The reasonable application method and strict surface treatment of the example ensure that the glaze is well combined with the base layer and exerts excellent performance. The construction of the comparative example is random and the surface treatment is simple, which affects the bonding strength and overall performance. The precise sintering parameter control of the example also helps to form a high-quality glaze layer.

[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An anti-seepage high-strength cement glaze, characterized in that: The invention comprises the following raw materials in parts by weight: 20-35 parts of wollastonite, 15-25 parts of diopside, 8-15 parts of spodumene, 5-12 parts of kaolin, 3-8 parts of quartz sand, 2-6 parts of alumina powder, 1-4 parts of zirconium oxide powder, 0.5-1.5 parts of water reducing agent, 0.3-1 parts of film-forming aid, 0.1-0.5 parts of defoaming agent, 0.2-0.8 parts of dispersant, 0.3-0.9 parts of thickener and 15-25 parts of water; The silicon dioxide content of the wollastonite is not less than 90%, the calcium and magnesium content of the diopside is not less than 30%, the lithium oxide content of the spodumene is not less than 4%, the whiteness of the kaolin is not less than 85%, the silicon dioxide content of the quartz sand is not less than 98%, the particle size of the alumina micropowder is 5-15μm, and the particle size of the zirconium oxide micropowder is 3-10μm. After the cement glaze is applied on the surface of the building material, it is sintered at a high temperature of 1150-1250°C to form a glaze layer with a thickness of 0.3-0.8mm, a compressive strength of not less than 120MPa, a permeability level of not less than P15, a bonding strength with the cement base of not less than 2.5MPa, a surface hardness of not less than 7H, and a wear resistance of not more than 0.1g / cm 2 , Chemical corrosion resistance: After immersion in acid and alkali solution with a pH value of 2-13 for 28 days, there is no obvious change in the glaze surface, and the mass loss rate does not exceed 0.3%.

2. The anti-seepage high-strength cement glaze according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer, the solid content of which is not less than 40%, and the molecular structure of which contains carboxyl and sulfonic acid functional groups; The film-forming aid is alcohol ester dodecanedione with a purity of not less than 99%; The defoamer is an organosilicon defoamer, and the content of active ingredients is not less than 95%; The dispersant is sodium hexametaphosphate with a purity of not less than 95%; The thickener is hydroxyethyl cellulose with a viscosity of 20000-40000 mPa·s, and is used to adjust the rheological properties of the glaze.

3. The anti-seepage high-strength cement glaze according to claim 1, characterized in that: It also includes 0.5-2 parts of nano titanium dioxide, the particle size of the nano titanium dioxide is 20-50nm; It contains 0.2-1 parts of rare earth oxide, which is a mixture of cerium oxide and lanthanum oxide in a mass ratio of 1:1-2:

1. The rare earth oxide is used to improve the high temperature resistance and anti-aging performance of the glaze.

4. A method for preparing the anti-seepage high-strength cement glaze according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Accurately weigh the raw materials according to the formula, put wollastonite, diopside, spodumene, kaolin, quartz sand, alumina powder and zirconium oxide powder into a high-speed mixer at a stirring speed of 300-500r / min for 10-20 minutes to perform preliminary mixing; Step 2: Add water reducing agent, film-forming aid, defoamer, dispersant, thickener and water to the preliminarily mixed materials, and then stir at a high speed of 500-800r / min for 20-40 minutes to obtain a uniform glaze slurry; Step 3: Transfer the glaze slurry to a ball mill, the speed of the ball mill is 200-300r / min, the ball milling time is 3-6 hours, the ball milling medium is zirconia balls, the ball diameter is 5-10mm, the ball-to-material ratio is 3:1-5:1, and fine grinding is performed; Step 4: The ball-milled glaze slurry is filtered through an 80-100 mesh screen to remove impurities, and then subjected to vacuum degassing treatment at a vacuum degree of 0.06-0.09 MPa for 10-20 minutes to eliminate bubbles in the slurry and obtain the final cement glaze.

5. The method for preparing the anti-seepage high-strength cement glaze according to claim 4, characterized in that: In step 1, the raw materials are preheated before being put into the high-speed mixer, the preheating temperature is 80-120°C, and the preheating time is 30-60 minutes; In step 2, water is magnetized before being added, the magnetization magnetic field strength is 0.3-0.6T, and the magnetization time is 10-20 minutes.

6. The method for preparing the anti-seepage high-strength cement glaze according to claim 4, characterized in that: In step 3, a temperature monitoring device is provided in the ball mill. When the ball mill temperature exceeds 50°C, the cooling system is started. The cooling system uses circulating water cooling to control the ball mill temperature below 50°C. During the ball milling process, a grinding aid is added into the ball mill every 1-2 hours. The grinding aid is calcium stearate, and the added amount is 0.1-0.3% of the total weight of the raw materials.

7. The method for preparing the anti-seepage high-strength cement glaze according to claim 4, characterized in that: In step 4, the glaze slurry after vacuum degassing is aged at 20-30° C. for 24-48 hours, and is slowly stirred every 6-12 hours during the aging process at a stirring speed of 50-80 r / min; Before using the aged glaze, pigments are added to adjust the color according to construction requirements and environmental conditions. The pigments are inorganic pigments, including iron oxide, cobalt oxide or copper oxide. The amount of pigment added is 0.5-5% of the total weight of the glaze.

8. The method for preparing the anti-seepage high-strength cement glaze according to claim 4, characterized in that: Cement glaze is applied on the surface of cement products, including cement bricks, cement boards, and cement pipes, by spraying, brushing, or rolling. The thickness is controlled between 0.3-0.8mm according to specific needs. Before applying the glaze, the surface of the cement product needs to be pre-treated. First, remove the dust, oil and impurities on the surface, then rinse it with clean water and then polish it.

9. The method for preparing the anti-seepage high-strength cement glaze according to claim 4, characterized in that: After the glaze is applied, the cement product is naturally dried at room temperature for 2-4 hours, and then placed in a high-temperature kiln for sintering. The sintering heating rate is 5-10℃ / min, and the temperature is kept at 1150-1250℃ for 2-4 hours, and then cooled to room temperature at a cooling rate of 3-6℃ / min; During the sintering process, the atmosphere in the kiln can be controlled as needed, including using an oxidizing atmosphere or a reducing atmosphere to adjust the color and properties of the glaze. The oxygen content in the oxidizing atmosphere is controlled at 8-15%, and the carbon monoxide content in the reducing atmosphere is controlled at 2-5%.

10. The method for preparing the anti-seepage high-strength cement glaze according to claim 4, characterized in that: The prepared anti-seepage high-strength cement glaze is used in building exterior walls, floors, pools, bathrooms and other places that require anti-seepage, high strength, wear resistance and chemical corrosion resistance; The cement glaze is compatible with thermal insulation materials and decorative materials, and can be used in combination to form a multifunctional building structure system.

Citation Information

Patent Citations

  • Method for preparing ultralow-temperature quickly-fired vitrified ceramic brick

    CN102875155A

  • Cement tile

    CN105130501A

  • Manufacturing method of glazed cement product

    CN1061211A

  • Anti-wear and anti-corrosion concrete curb stone with glaze

    CN108358571A